The Relationship Between Financial Maturity (Financial Development) and the Effectiveness of Monetary Policy in Iraq (1990-2021) - Zainab Wissam Sami AL-Hafidh; Dr. Aws Fakhr Eldeen Ayoub El-Jwejatee (Migration Letters, 2023)
The research aims to study the relationship between financial maturity (financial development) and the effectiveness of monetary policy in Iraq and the relationship between financial maturity and the development of Gross Domestic Product (GDP). The study utilized the annual data in the form of time series for the period from (1990 to 2021). The transmission channels were identified through the money supply, the Consumer Price Index, and the Gross Domestic Product. The local credit standard was also used as a percentage of GDP as an independent variable. The data was analyzed using the static model, where the results of the preliminary tests and reading the graphic character of the variables showed the possibility of applying the ARDL model after verifying the conditions of its use. The test results showed a significant functional relationship between the Gross Domestic Product, the general level of consumer prices, and the broad money supply with financial maturity. This aligns with theoretical propositions that confirmed the validity of these relationships through measurement and estimation.